Reconceptualizing information quality as effective use in the context of business intelligence and analytics. (December 2019) - Torres, Russell; Sidorova, Anna
Abstract: Despite a significant body of knowledge related to BI&A success, questions remain regarding the mechanism through which BI&A contributes to organizational benefits. In this paper, we build on the representation theory of effective use in order to enrich the current understanding of BI&A success informed by the IS success model. The theoretical model proposed here casts an integrated construct, information-quality-as-effective-use, as the mediator between system quality, data quality, and BI&A personnel expertise and performance benefits. The results of the empirical testing support the propositions of the theoretical model. Implications for theory and practice are discussed.